Students’ Experiences in Suddenly Transformed Living and Educational Environments by COVID-19 - Hernández-Hernández, Fernando; Sancho-Gil, Juana M. (Frontiers in Psychology, 2021)
This paper builds on research about how university students felt affected by the Covid19 pandemic and, especially, by the irruption of non-face-to-face classes and mixed teaching methods in this context. How have young people experienced this situation? How has it affected their wellbeing and the learning strategies should develop have had to incorporate into their virtual relationships? their virtual relationships? How have they related and relate to virtual tools for a task that they have always experienced face-to-face? To answer these questions, the TRAY-AP project that investigates how university students learn collected 89 scenes that show the effects of the Covid 19 on their lives and the university. We grouped these scenes into seven key concepts to detect how students were emotionally affected, especially by moving from face-to-face to virtual learning. From this analysis, although primarily negative, the emotional effects have also allowed them to generate positive strategies for readaptation and collaboration with other colleagues. All of which opens the way to rethink the predominant pedagogical and knowledge relations in the university.